2021
DOI: 10.1016/j.clnu.2021.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength as a surrogate marker of lean mass and risk of malnutrition in paediatric patients

Abstract: Background & aims: The use of handgrip strength (HGS) as a proxy of nutritional status in sick children has not been studied. This study created HGS centile charts in healthy children and explored the utility of HGS z-scores as markers of body composition and screening of malnutrition risk in sick children. Methods: Data from 535 healthy children aged 5e16 years were used for the development of HGS centiles adjusted either for age or height. In 595 sick children, relationships between HGS z-scores with body co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Importantly, physical outcome measures were never worse for patients who had been exposed to an early macronutrient deficit in the PICU under the late-PN strategy, as compared with early full feeding of patients under the early-PN strategy. This is reassuring in view of the documented association between malnutrition in children and poorer physical function, such as lower handgrip strength [ 21 23 ], and further endorses de-implementation of the use of early-PN in the PICU. The present study also showed that, unfortunately, late-PN also did not improve any measure of physical function, unlike previously demonstrated beneficial effects on several measures of neurocognitive functioning and emotional and behavioral problems [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Importantly, physical outcome measures were never worse for patients who had been exposed to an early macronutrient deficit in the PICU under the late-PN strategy, as compared with early full feeding of patients under the early-PN strategy. This is reassuring in view of the documented association between malnutrition in children and poorer physical function, such as lower handgrip strength [ 21 23 ], and further endorses de-implementation of the use of early-PN in the PICU. The present study also showed that, unfortunately, late-PN also did not improve any measure of physical function, unlike previously demonstrated beneficial effects on several measures of neurocognitive functioning and emotional and behavioral problems [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 74%
“…This study had first shown that, as compared with initiating parenteral nutrition (PN) within 24 h after admission to supplement insufficient enteral nutrition (early-PN), withholding of supplemental PN in the first week in the PICU (late-PN) improved short-term PICU outcomes [ 17 ]. However, as underfeeding has been related to worse cognitive performance, behavioral problems, and impaired physical development of otherwise healthy children [ 18 23 ], there were concerns about potential adverse long-term consequences of the low caloric and macronutrient intake with late-PN for health and physical and neurocognitive development. Therefore, patients were invited for an extensive investigation of these outcomes 2 and 4 years after PICU admission, in comparison with healthy children.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we currently do not know whether dynapenia concurs with muscle mass loss in children with CKD. Muscle strength was significantly correlated to muscle mass in a recent pediatric study [ 60 ], while muscle force relative to muscle size was reduced in a study evaluating muscle torque to calf muscle cross-sectional area [ 61 ].…”
Section: Muscle Wasting and Outcomes In Children With Ckdmentioning
confidence: 99%
“…Handgrip strength (HGS) is an economical and field-friendly tool that provides an indirect measure of FFM, muscular strength, and malnutrition status of an individual [52,53]. HGS measures are obtained by using a dynamometer, where the individual fully exerts their strength by squeezing the dynamometer with their dominant hand to measure grip pressure [53].…”
Section: Handgrip Strength (Hgs)mentioning
confidence: 99%